The N-terminal Domain of NPC1L1 Protein Binds Cholesterol and Plays Essential Roles in Cholesterol Uptake - Zhang, Jin-Hui (American Society for Biochemistry and Molecular Biology, 2011)
Niemann-Pick C1-like 1 (NPC1L1) is a multitransmembrane protein playing a crucial role in dietary and biliary cholesterol absorption. Cholesterol promotes the formation and endocytosis of NPC1L1-flotillin-cholesterol membrane microdomains, which is an early step in cholesterol uptake. How cholesterol is sensed in this step is unknown. Here, we find that the N-terminal domain (NTD) of NPC1L1 binds cholesterol. Mutation of residue Leu-216 in NPC1L1-NTD eliminates cholesterol binding, decreases the formation of NPC1L1-flotillin-cholesterol membrane microdomains, and prevents NPC1L1-mediated cholesterol uptake in culture cells and mice livers. NPC1L1-NTD specifically binds cholesterol but not plant sterols, which may account for the selective cholesterol absorption in intestine. Furthermore, 25- or 27-hydroxycholesterol competes with cholesterol to bind NPC1L1-NTD and inhibits the cholesterol induced endocytosis of NPC1L1. Together, these results demonstrate that plasma membrane-localized NPC1L1 binds exogenous cholesterol via its NTD, and facilitates the formation of NPC1L1-flotillin-cholesterol membrane microdomains that are then internalized into cells through the clathrin-AP2 pathway. Our study uncovers the mechanism of cholesterol sensing by NPC1L1 and proposes a mechanism for selective cholesterol absorption.